Imaging Techniques: Essential Tools for the Study of SARS-CoV-2 Infection - Deroubaix, Aurélie; Kramvis, Anna (Frontiers in Cellular and Infection Microbiology, 2022)
The world has seen the emergence of a new virus in 2019, SARS-CoV-2, causing the COVID-19 pandemic and millions of deaths worldwide. Microscopy can be much more informative than conventional detection methods such as RT-PCR. This review aims to present the up-to-date microscopy observations in patients, the in vitro studies of the virus and viral proteins and their interaction with their host, discuss the microscopy techniques for detection and study of SARS-CoV-2, and summarize the reagents used for SARS-CoV-2 detection. From basic fluorescence microscopy to high resolution techniques and combined technologies, this article shows the power and the potential of microscopy techniques, especially in the field of virology.